A Comparison of Different Multi-Criteria Analyses for Electric Vehicle Charging Station Deployment - Rouyendegh (B. Erdebilli), Babak Daneshvar; Dogru, Cem Isik; Aybirdi, Canan Basak (Communications in Mathematics and Applications, 2019)
Scarcity in near future, and the price fluctuation of fossil fuels lead to many industries change their products that use these resources into more eco-friendly versions. One of the most recent and noticeable example of this situation is the automobile industry. As a result of this, electric vehicles have started to become more popular and their sales increase substantially. Since these electric vehicles have a limited range for transportation before they require charging, the number and the positions of charging units become very important. In this study, we consider a electric vehicle (EV) charging station (CS) placement problem which aims to maximize users' utility. To deal with these problem, we survey to find the weights of criterion, which are selected as accessibility, traffic convenience and waiting time calculated by AHP method and VIKOR and TOPSIS methods are used to evaluate each alternative. As a main tool for charging station deployment, an integer programming model, which maximizes electric vehicle driver's utility in term of evaluation results, is developed and the effects of different evaluation techniques on deployment procedure is shown and compared.